In Their Own Voices: First Nations Students Identify Some Cultural Mediators of Their Learning in the Formal School System - Kanu, Yatta (Alberta Journal of Educational Research, 2002)
Theories of cognition argue that children develop thinking, communication, learning, and motivational styles consistent with the culture into which they are socialized. Cultural socialization, therefore, influences how students learn, particularly how students mediate, negotiate, and respond to curriculum materials, instructional strategies, learning tasks, and communication patterns in the classroom. But what specific aspects of culture influence the learning of a particular group of students? The author set out to answer this question in relation to First Nations students by conducting research among First Nations students in a Winnipeg high school. Five culturally relevant themes were identified that provide insights into the development of appropriate instruction for preservice teachers for the enhancement of cross-cultural communication, the design and implementation of assessment strategies, and the creation of effective instructional materials. These are traditional Aboriginal approaches to learning, patterns of oral interaction, concepts of self, curriculum relevance, and the educator's interpersonal style.